2022
DOI: 10.1038/s41589-022-01034-2
|View full text |Cite
|
Sign up to set email alerts
|

Scalable biological signal recording in mammalian cells using Cas12a base editors

Abstract: Biological signal recording enables the study of molecular inputs experienced throughout cellular history. However, current methods are limited in their ability to scale up beyond a single signal in mammalian contexts. Here, we develop an approach using a hyper-efficient dCas12a base editor for multi-signal parallel recording in human cells. We link signals of interest to expression of guide RNAs to catalyze specific nucleotide conversions as a permanent record, enabled by Cas12’s guide-processing abilities. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…60,64 Mutations in catalytic sites can generate a nickase or catalytically dead Cas protein (dCas12a and dCas9), which can be fused with additional modulators to achieve site-specic transcription activation/ repression, base editing and so on. [14][15][16]18,20,21,65,66 Recently, the split-protein strategy and a chemically controlled autoinhibited RNA switch have been used to engineer temporally controlled Cas protein-based effectors responding to light or ligands. 17,19,[22][23][24][25][26] We speculated that the response speed of temporally controlled Cas protein-based effectors might be adjustable by modifying their non-specic DNA binding sites.…”
Section: Critical Residues Mediating 1d Diffusion Of Cas12amentioning
confidence: 99%
See 2 more Smart Citations
“…60,64 Mutations in catalytic sites can generate a nickase or catalytically dead Cas protein (dCas12a and dCas9), which can be fused with additional modulators to achieve site-specic transcription activation/ repression, base editing and so on. [14][15][16]18,20,21,65,66 Recently, the split-protein strategy and a chemically controlled autoinhibited RNA switch have been used to engineer temporally controlled Cas protein-based effectors responding to light or ligands. 17,19,[22][23][24][25][26] We speculated that the response speed of temporally controlled Cas protein-based effectors might be adjustable by modifying their non-specic DNA binding sites.…”
Section: Critical Residues Mediating 1d Diffusion Of Cas12amentioning
confidence: 99%
“…8–13 In addition, dead Cas9 (dCas9), Cas9 nickase (nCas9) and dead Cas12a (dCas12a) have been engineered by mutating their nuclease domains while retaining their RNA-guided DNA-binding activities, which can be fused with other effector proteins and be repurposed for gene regulation, base editing, prime editing and so on. 14–21 Using split-Cas9 proteins or guide RNAs with unique structural elements, the activity of Cas9 and Cas12a can be switched on by chemical or optical inputs. 22–27…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The much shorter guide RNA required by Cas12a compared to Cas9 is a relatively minor but non-negligible advantage, in terms of both delivery and cost. Potentially, more important is the ability of Cas12a to process pre-crRNA, which provides for multiplexing, that is, co-expression of several guides on a single transcript for compact delivery, expression under inducible or state-dependent promoters, or for monitoring of gene expression . Indeed, highly efficient, multiplex, simultaneous genome editing of dozens of targets using Cas12a has been repeatedly demonstrated. , Moreover, efficient simultaneous regulation of multiple genes in mammalian cells by multiplexing with inactivated Cas12a has been reported by several groups. Several studies have reported high specificity of Cas12a, with an extremely low off-target rate.…”
Section: Harnessing Class 2 Crispr Diversity For Applications In Geno...mentioning
confidence: 99%
“…The facile information storage enabled by cat-RNA has several advantages compared with existing memory systems (43)(44)(45)(46)(47)(48)(49). First, cat-RNA records information within universally-expressed biomolecules at highly conserved sequences adjacent to variable sequences that can be used to distinguish taxa (50).…”
Section: Main Textmentioning
confidence: 99%